The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1080/0361526x.2011.580422
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the International Visibility, Quality, and Impact of Journals Published in Tanzania

Abstract: This study investigated the international visibility, quality, and impact of journals published in Tanzania. The objective of the study was to determine the extent to which the journals are internationally visible, their compliance with publishing standards, and the impact they have made to the academic community. A total of 31 journals from 12 institutions were involved in the study. The questionnaire, interview, observation and database searches were used in data collection. The study found that most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In terms of countries, Egypt (15) and South Africa (15) had same number of journals, followed by Nigeria (8), on the top 20 list of journals with highest Google scholar H5-Index Table 3. Only 19 health sciences journals from Africa have their JIF calculated for 2022.…”
Section: Top 10 and Top 20 African Health Science Journalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of countries, Egypt (15) and South Africa (15) had same number of journals, followed by Nigeria (8), on the top 20 list of journals with highest Google scholar H5-Index Table 3. Only 19 health sciences journals from Africa have their JIF calculated for 2022.…”
Section: Top 10 and Top 20 African Health Science Journalsmentioning
confidence: 99%
“…This is mostly because there are few African journals included in the international citation databases [ 1 , 3 , 4 ], which reduces the visibility of the continent’s health science research. Several studies have reported an increase in scientific impact following indexing of journals in international and regional citation databases as it increases visibility [ 5 8 ]. Likewise, indexing status of a journal is one of the factors that influences author’s selection of journal to publish with.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that research and publishing is an important role of academic librarians, these findings reveal that they do not conduct enough research and, thus, published less. Previously, Msuya and Muneja (2011) and Sendikakawa (2005) reported that the state of LIS research and publishing in East African is very low with only a few renowned professionals publishing a lot, whereas many others publish very little. This is contrary to what has been reported from other African countries such as Nigeria.…”
Section: Growth Of Lis Scholarly Literature In Tanzaniamentioning
confidence: 99%